Case Report: Real NPSLE? A patient with systemic sclerosis overlapping systemic lupus erythematosus presenting as epilepsy - Zhang, Jialin; Wu, Xiaodong; Xue, Jing; Liu, Lei (Frontiers in Immunology, 2023)
Neuropsychiatric systemic lupus erythematosus (NPSLE) is the diagnosis that rheumatologists most often need to consider when a patient with lupus presents with neurologic symptoms. However, neurological involvement is rare in systemic sclerosis (SSc), and high doses of steroids tend to trigger scleroderma renal crisis (SRC). When a patient with SSc overlapping SLE presents with epilepsy and renal crisis, the exact diagnosis and whether to initiate high-dose glucocorticoid therapy are questions to ponder. Here, we report a patient with overlap syndrome (SSc overlapping SLE), who developed CNS symptoms, and improved after treatment against SRC after excluding NPSLE. We report this case with the aim of arousing the attention of rheumatologists to SSc and SRC-related encephalopathy when SSc was overlapped with SLE.